Analisis Keterampilan Siswa Melalui Pengembangan Model Pembelajaran Kimia Berbasis Simulator Pada Pengujian pH - Faisal Akbar Ramdhani; Mutia Amaliyah; Salwa Widya Hanifah; Zildjian Naura Rahman (International Forum of Researchers and Lecturers, 2024)
The influence of the development of Science and Technology (IPTEK) on the world of education, so that both teachers and students are required to always adapt to existing developments. Technology is the result of knowledge originating from the world of education therefore the world of education should utilize technology to increase efficiency in learning. Chemistry among students is still considered material that is difficult to understand. One of its attractions is the abstract nature of chemical material. Chemistry learning does not only include theoretical learning but also includes practical activities. This research was carried out to determine the effect of using a virtual laboratory on students' skills during direct practicum. The method used in this research is a quantitative method that uses a lot of numbers, starting from data collection, interpretation of the data and presentation of the results. A total of 52 students in class XI, Department of Mathematics and Natural Sciences at SMA Negeri 1 Sliyeg. Presenting the results in the form of a representative table will increase the reader's level of understanding and make it easier to access information. Virtual laboratories help students understand the practical process. Based on the results of data analysis obtained from filling out the questionnaire, it was found that 78.8% or the majority of students answered agreeing that the virtual laboratory had an effect on increasing pH testing. This proves that the use of virtual laboratories can be a way out so that when doing direct practicum students do not experience difficulties and the practicum runs more effectively.